1984
DOI: 10.1042/bj2230911
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, transport and processing of myeloperoxidase in the human leukaemic promyelocytic cell line HL-60 and normal marrow cells

Abstract: The processing and intracellular transport of myeloperoxidase were studied in the human promyelocytic leukaemia cell line HL-60 and in normal marrow cells labelled with [35S]methionine or [14C]leucine. Myeloperoxidase was precipitated with antimyeloperoxidase serum; the immunoprecipitates were subjected to sodium dodecyl sulphate/polyacrylamide-gel electrophoresis and radiolabelled myeloperoxidase visualized by fluorography. During a 1 h pulse, myeloperoxidase was labelled in a chain of apparent Mr 90 000. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 24 publications
3
42
0
1
Order By: Relevance
“…Calreticulin, a calcium-binding protein that resides in the ER, has been suggested to function as a molecular chaperone and facilitate the critical folding of apopro-MPO to allow insertion of heme followed by conversion to pro-MPO (14). The stepwise processing of pro-MPO has been investigated in myeloid cells (10,(15)(16)(17)(18)(19)(20), and the results obtained are consistent with those later deduced from cDNA sequence data. Thus, during subsequent processing of pro-MPO the amino-terminal propeptide, a small peptide between the light and heavy chains, and a single serine residue at the carboxyl-terminal are removed (21).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Calreticulin, a calcium-binding protein that resides in the ER, has been suggested to function as a molecular chaperone and facilitate the critical folding of apopro-MPO to allow insertion of heme followed by conversion to pro-MPO (14). The stepwise processing of pro-MPO has been investigated in myeloid cells (10,(15)(16)(17)(18)(19)(20), and the results obtained are consistent with those later deduced from cDNA sequence data. Thus, during subsequent processing of pro-MPO the amino-terminal propeptide, a small peptide between the light and heavy chains, and a single serine residue at the carboxyl-terminal are removed (21).…”
supporting
confidence: 74%
“…Thus, during subsequent processing of pro-MPO the amino-terminal propeptide, a small peptide between the light and heavy chains, and a single serine residue at the carboxyl-terminal are removed (21). Intermedi-ate processing forms have been observed with molecular masses of 81 and 74 kDa (10,18,19,22) of which the smaller can be converted directly into mature MPO after cleavage between the heavy and the light subunit (19,22). This finding suggests that the amino-terminal propeptide, which does not seem to be part of the 74-kDa form, is removed during an intermediate step before final processing.…”
mentioning
confidence: 99%
“…Studies on the biosynthesis of MPO have shown that these large and small subunits are generated from a single polypeptide chain precursor (Yamada, 1982;Olsson et al, 1984;Koeffler et al, 1985;Akin and Kinkade, 1986). Our present study provided evidence that MPO is synthesized from a gene located on chromosome 17.…”
Section: Discussionmentioning
confidence: 99%
“…Mature MPO can be chemically cleaved into hemimyeloperoxidase, a single heavy-light protomer with the same specific activity as the holoenzyme [31,36], although it is not known if such forms are produced in vivo. Despite significant work on the biosynthesis of MPO [37][38][39][40][41][42][43][44][45][46][47] there is limited insight into the assembly and transport of mature MPO. Taylor et al [38] demonstrated that proMPO undergoes proteolytic processing before dimerization and that assembly is a late event in MPO biosynthesis.…”
Section: Discussionmentioning
confidence: 99%